2000
DOI: 10.1029/1999gl011025
|View full text |Cite
|
Sign up to set email alerts
|

Cl and Br atom concentrations during a surface boundary layer ozone depletion event in the Canadian High Arctic

Abstract: Abstract. C2-Cs hydrocarbons were measured in situ at Alert, Nunavut, Canada from April 14 to May 10, 1998 at a minimum frequency of 12 samples per day. During the sampling period, an event occurred where the O3 mixing ratio fell from about 15 ppbv to the instrumental detection limit of less than I ppbv in a timespan of about 24 hours. Mixing ratios of alkanes and ethyne decreased concurrently with the O3 decrease. Ancillary data suggested that this was essentially due to chemical reactions only, most probably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
103
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(112 citation statements)
references
References 17 publications
7
103
2
Order By: Relevance
“…1a; Liao et al, 2014). The model predicts Cl atom concentrations of 2 × 10 5 to 6 × 10 5 molecules cm −3 , which is also higher than previous estimates of 1 × 10 3 to 1 × 10 5 determined from hydrocarbon measurements (Jobson et al, 1994;Ariya et al, 1998;Rudolph et al, 1999;Boudries and Bottenheim, 2000;Keil and Shepson, 2006). As discussed in Stephens et al (2012), the hydrocarbon-based methods average over the transport path, which can be aloft and consist of several days, and thus should be lower than that observed near the surface, if the surface is the Cl 2 and Br 2 source.…”
Section: Comparison Of Modeled and Observed Mole Ratios For Select Spcontrasting
confidence: 51%
See 1 more Smart Citation
“…1a; Liao et al, 2014). The model predicts Cl atom concentrations of 2 × 10 5 to 6 × 10 5 molecules cm −3 , which is also higher than previous estimates of 1 × 10 3 to 1 × 10 5 determined from hydrocarbon measurements (Jobson et al, 1994;Ariya et al, 1998;Rudolph et al, 1999;Boudries and Bottenheim, 2000;Keil and Shepson, 2006). As discussed in Stephens et al (2012), the hydrocarbon-based methods average over the transport path, which can be aloft and consist of several days, and thus should be lower than that observed near the surface, if the surface is the Cl 2 and Br 2 source.…”
Section: Comparison Of Modeled and Observed Mole Ratios For Select Spcontrasting
confidence: 51%
“…Unlike bromine, chlorine radicals efficiently oxidize a wide range of pollutants and volatile organic compounds (VOCs), often with faster rate coefficients than analogous reactions by the hydroxyl radical (OH); thus, chlorine has an abundance of atmospheric sinks. Estimates of polar region Cl atom concentrations using hydrocarbon decay methods are typically in the range of 10 4 -10 5 molecules cm −3 (Jobson et al, 1994;Ariya et al, 1998;Boudries and Bottenheim, 2000), approximately 2-3 orders of magnitude lower than analogous estimates of Br (Cavender et al, 2008).…”
Section: Introductionmentioning
confidence: 87%
“…This deposition, associated with air masses transported over sea ice and snow during polar winter, results in a sudden outburst of bromine reactivity at polar sunrise, leading to destruction of the surface ozone layer. Measurements show that bromine chemistry is strongly enhanced compared to the sea water Br:Cl molar ratio [104][105][106]. It is natural to assume that, similarly as in the case of tropospheric aqueous sea salt aerosols, processes at the liquid surface of snow packs sprayed with sea water may play an important role [55].…”
Section: Atmospheric Applicationsmentioning
confidence: 99%
“…[9][10][11][12][13][14] Mercury depletion events seem to correlate with tropospheric ozone reduction, [9-11, 13, 14] which is known to be a result of the catalytic destruction of ozone molecules by chlorine and bromine atoms, thus yielding molecular oxygen and ClO or BrO. [15][16][17] In this connection, the reaction Hg + BrO!HgO + Br has been proposed as an important path for mercury depletion in the troposphere. [10,13,16] Various authors have pointed out that the experimentally derived stability of gaseous HgO is seriously in error [18,19] and that by correcting for this error there is no chance that elemental Hg can be oxidized by BrO or other related oxidants in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] In this connection, the reaction Hg + BrO!HgO + Br has been proposed as an important path for mercury depletion in the troposphere. [10,13,16] Various authors have pointed out that the experimentally derived stability of gaseous HgO is seriously in error [18,19] and that by correcting for this error there is no chance that elemental Hg can be oxidized by BrO or other related oxidants in the atmosphere. Filatov and Cremer [19] have shown that observations made with regard to the stability of HgO and its bond dissociation energy (BDE) may also apply to stability and bonding of other mercury chalcogenides HgE.…”
Section: Introductionmentioning
confidence: 99%